2014
DOI: 10.1111/pbr.12158
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a new set of 164 polymorphic ESTSSR markers for diversity and breeding studies in rubber tree (Hevea brasiliensis Müll. Arg.)

Abstract: Despite its economic importance and recent genome release, the need for molecular tools for Hevea brasiliensis is high. In the frame of a disease resistance study, EST sequences were retrieved from public database or generated by sequencing SSH libraries. Sequences were trimmed and microsatellite motifs searched using an ad hoc bioinformatic pipeline, and pairs of primers for the amplification of candidate markers were generated. We found a total of 10 499 unigenes from both sources of sequences, and 673 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…However, in the preliminary analysis in the present study, the goodness‐of‐fit of the model with a mean value of μ = 5 × 10 –4 was poor. Furthermore, the mutation rate for EST‐SSR is generally lower than that for genomic SSR (Cubry et al, 2014). Therefore, we used 1 × 10 –4 as the mean value of μ .…”
Section: Methodsmentioning
confidence: 99%
“…However, in the preliminary analysis in the present study, the goodness‐of‐fit of the model with a mean value of μ = 5 × 10 –4 was poor. Furthermore, the mutation rate for EST‐SSR is generally lower than that for genomic SSR (Cubry et al, 2014). Therefore, we used 1 × 10 –4 as the mean value of μ .…”
Section: Methodsmentioning
confidence: 99%
“…A high frequency of trinucleotide repeats is reported in exons that contain almost no tetranucleotide repeats (Toth et al 2000;Varshney et al 2005), whereas mutability tests showed that the allelic variability of exon SSRs is lower than that of intronic repeats (Li et al 2011). Massive EST and genomic sequence data have made available information on repeat region abundance and position, and bioinformatic analyses have significantly accelerated the process of identification and selection, reducing the time for their application (Acuna et al 2012;Li et al 2012;Shiferaw et al 2012;Yang et al 2012;Duran et al 2013;Cubry et al 2014).…”
Section: Communicated By G G Vendraminmentioning
confidence: 99%
“…Molecular markers have been used to assess genetic diversity through indices such as expected and observed heterozygosity and fixation index, among others. Some studies have quantified the genetic diversity of rubber trees using these markers (CUBRY et al, 2014;PERSEGUINI et al, 2012;PETHIN et al, 2015), offering significant potential for genetic studies involving the species (SOUZA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%